DEVELOPMENT OF AN EFFECTIVE SCHEME OF OPERATION OF VOLUMETRIC HYDROURITMA IN HYDRAULIC SYSTEMS OF MINING MACHINES (Web of Technology: Multidimensional Research Journal, 2024)
It is now widely used in mining, construction and agriculture with a hydraulic system from a number of machines and equipment. In order to increase the stable and reliable operation of hydraulic systems of these machines, it is important to develop the correct prinspial schemes for them, this article presents analyzes on the basis of the development of the prinspial scheme of hydraulic operation of volumetric pumping devices.